Lasting and Sex-Dependent Impact of Maternal Immune Activation on Molecular Pathways of the Amygdala - Keever, Marissa R.; Zhang, Pan; Bolt, Courtni R.; Antonson, Adrienne M.; Rymut, Haley E.; Caputo, Megan P.; Houser, Alexandra K.; Hernandez, Alvaro G.; Southey, Bruce R.; Rund, Laurie A.; Johnson, Rodney W.; Rodriguez-Zas, Sandra L. (Frontiers in Neuroscience, 2020)
The prolonged and sex-dependent impact of maternal immune activation (MIA) during gestation on the molecular pathways of the amygdala, a brain region that influences social, emotional, and other behaviors, is only partially understood. To address this gap, we investigated the effects of viral-elicited MIA during gestation on the amygdala transcriptome of pigs, a species of high molecular and developmental homology to humans. Gene expression levels were measured using RNA-Seq on the amygdala for 3-week old female and male offspring from MIA and control groups. Among the 403 genes that exhibited significant MIA effect, a prevalence of differentially expressed genes annotated to the neuroactive ligand-receptor pathway, glutamatergic functions, neuropeptide systems, and cilium morphogenesis were uncovered. Genes in these categories included corticotropin releasing hormone receptor 2, glutamate metabotropic receptor 4, glycoprotein hormones, alpha polypeptide, parathyroid hormone 1 receptor, vasointestinal peptide receptor 2, neurotensin, proenkephalin, and gastrin releasing peptide. These categories and genes have been associated with the MIA-related human neurodevelopmental disorders including schizophrenia and autism spectrum disorders. Gene network reconstruction highlighted differential vulnerability to MIA effects between sexes. Our results advance the understanding necessary for the development of multifactorial therapies targeting immune modulation and neurochemical dysfunction that can ameliorate the effects of MIA on the offspring behavior later in life.